Main Ideas and Specific Areas of Priestly Formation according to Ratio institutionis sacerdotalis pro Polonia (2021) - Rabczyński, Paweł (Studia Warmińskie, 2023)
The article outlines the main ideas and specific areas of formation for priests according to Ratio institutionis sacerdotalis pro Polonia from 2021. These pertain to the entire formation of priests, both during the preparation for the reception of the sacrament of Holy Orders (initial, seminary formation) and after receiving it (permanent, ongoing formation). The context of the topic is the current vocational situation in Poland, which is largely shaped by the contemporary culture of transience. The Ratio pro Polonia defines four fundamental characteristics of the entire formation path of priests: unity, communality, missionary spirit, and integrity. They serve as both principles and criteria for formation. The document consistently shows the primacy of God in the lives, formation, and ministry of those called to the priesthood and emphasizes the need for continuous growth in their relationship with God and with people. Renewed principles and norms of priestly formation emphasize its dynamism and highly personal character. The grace of the sacrament of Holy Orders and the identity of priests are constant points of reference in the formation process. The specific areas of formation for priests include education in celibacy, obedience, and poverty. Practicing these highlighted virtues is an imitation of Jesus Christ himself and serves priests in deepening their pastoral love for sisters and brothers.